2016
DOI: 10.1016/j.sjbs.2015.06.012
|View full text |Cite
|
Sign up to set email alerts
|

One-step synthesis of interpenetrating network hydrogels: Environment sensitivities and drug delivery properties

Abstract: A novel interpenetrating network hydrogel for drug controlled release, composed of modified poly(aspartic acid) (KPAsp) and carboxymethyl chitosan (CMCTS), was prepared in aqueous system. The surface morphology and composition of hydrogels were characterized by SEM and FTIR. The swelling properties of KPAsp, KPAsp/CMCTS semi-IPN and KPAsp/CMCTS IPN hydrogels were investigated and the swelling dynamics of the hydrogels was analyzed based on the Fickian equation. The pH, temperature and salt sensitivities of hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…These mixtures contributed both swelling and mechanical strength, although no synergy was detected, and each individual polymer retained its own intrinsic properties. ,, Another approach is to prepare semi-IPNs as a single solution to obtain a greater synergy. In the formation of semi-IPNs, a cross-linked polymer is normally mixed with a non-cross-linked polymer, followed by the in situ cross-linking of the later. ,, This method enhances the structural features of the network, giving rise to high water retention even under mechanical stress, which is lacking in neat IPN systems. Most of the literature suggesting semi-IPNs relates however to the preparation of limited amounts of hydrogels for drug-delivery applications. These semi-IPNs thus contain a substantial amount of synthetic polymer since the area of use does not require the development of large-scale inexpensive biobased SAP materials.…”
Section: Functionalization Of Proteins For Improving Water Affinitymentioning
confidence: 99%
“…These mixtures contributed both swelling and mechanical strength, although no synergy was detected, and each individual polymer retained its own intrinsic properties. ,, Another approach is to prepare semi-IPNs as a single solution to obtain a greater synergy. In the formation of semi-IPNs, a cross-linked polymer is normally mixed with a non-cross-linked polymer, followed by the in situ cross-linking of the later. ,, This method enhances the structural features of the network, giving rise to high water retention even under mechanical stress, which is lacking in neat IPN systems. Most of the literature suggesting semi-IPNs relates however to the preparation of limited amounts of hydrogels for drug-delivery applications. These semi-IPNs thus contain a substantial amount of synthetic polymer since the area of use does not require the development of large-scale inexpensive biobased SAP materials.…”
Section: Functionalization Of Proteins For Improving Water Affinitymentioning
confidence: 99%
“…Recently, a number of preclinical and clinical research studies indicated that GbE has many positive effects, such as scavenging radicals, anti-oxidation, antitumor, and protective effects in the central nervous system, and therapeutic effects for cerebral and peripheral vascular diseases (Li et al, 2012, Liu et al, 2009, Lu et al, 2016, Koltermann et al, 2007). These benefits of GbE are presumed to result from the synergistic effect of two distinct groups of compounds: the flavonoids (quercetin, kaempferol, and isorhamnetin) and terpenoid lactones (bilobalide, ginkgolides A, B and C) (Chen et al, 2010, Chen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“… 15 The band at 1287 cm −1 (AAm –CH 2 vibrations) diminishes over 60 min, but then reappears as a stronger band at 1334 cm −1 (–N–H stretch) after 24 h, which corresponds to copolymerisation and imidisation. 134–136 A small broad band at ∼1223 cm −1 , corresponds to the –C–O–C– stretch, evolves beyond 24 h; although nothing is seen in the initial 1 h 137 …”
Section: Resultsmentioning
confidence: 99%